2019
DOI: 10.1002/csr.1829
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate social responsibility transparency on the financial performance, brand value, and sustainability level of IT companies

Abstract: The companies are aware of the impact that disseminating their corporate social responsibility (CSR) performance has on how shareholders or investors perceive them. This work analyses if disseminating CSR results affects their economic–financial results, their scores in open‐access sustainability ranking, their brand values, and also the credit ratings that agencies S&P and Moody's confer them. For this purpose, the only 13 companies of the IT sector occupying a top 100 brand rankings position were selected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 54 publications
1
36
0
Order By: Relevance
“…The International Sustainable Campus Network (ISCN) has published the best campus sustainability practices in its annual report since 2013 to show and promote sustainable development in higher education [7]. In the present day, universities keep signing declarations and agreements that do not result in changes while industry is increasingly held accountable for the impact of its activities on society [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The International Sustainable Campus Network (ISCN) has published the best campus sustainability practices in its annual report since 2013 to show and promote sustainable development in higher education [7]. In the present day, universities keep signing declarations and agreements that do not result in changes while industry is increasingly held accountable for the impact of its activities on society [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Agus and Salas (2017) evidenced how corporate social responsibility (CSR) strengths positively affect the brand value level from the Interbrand listing, and how CSR concerns adversely affect changes in brand value and brand ranking. Alcaide et al (2020) supported the relation between brand value and the CSR of IT companies. These authors used valuations of the three consultants, and concluded that Brand Finance considers CSR in brand value more than the other two consultants.…”
Section: The Most Well-known International Consultancy Companiesmentioning
confidence: 75%
“…More specifically, the initial population includes all companies having at least one brand indexed by Interbrand Best Global Brands Rankings for at least one year from 2013 to 2018. Consistent with prior literature (Alcaide González, De La Poza Plaza & Guadalajara Olmeda, 2020;Sotorrio & Sánchez, 2008;Torres, Bijmolt, Tribó, & Verhoef, 2012), Interbrand companies have been considered an ideal setting for researching issues related to CSR disclosure since they are exposed to increased reputational risks (Fehle, Fournier, Madden, & Shrider, 2008). Therefore, they are encouraged to preserve the value of the brand value, where the corporate reputation is enclosed.…”
Section: Sample Selection and Data Sourcesmentioning
confidence: 78%
“…A company's BV could be explained by several company-specific characteristics. In line with prior literature (Alcaide González et al, 2020;Melo and Galan, 2011;Torres et al, 2010;Wang et al, 2015), we control for company size (SIZE) by the natural logarithm of total assets; the market performance through Tobin's Q (MP); the financial performance through the ROE (FP) and the leverage through the ratio between the total debt and total assets (LEVERAGE).…”
Section: Control Variablesmentioning
confidence: 97%
See 1 more Smart Citation